Tumor immune microenvironment (TIME) to enhance antitumor immunity - Sajin Rajbhandary; Hari Dhakal; Sudip Shrestha (European Journal of Medical Research, 2023)
Abstract The tumor microenvironment is a result of dynamic interaction between different cellular and non-cellular components. In its essence it is not a solo performer, but an ensemble of performers that includes cancer cells, fibroblasts, myo-fibroblasts, endothelial cells and immune cells. The short review highlights important immune infiltrates within the tumor microenvironment that shape cytotoxic t lymphocyte (CTL)-rich immune hot and CTL-deficient immune cold tumors and novel strategies that have potential role in enhancing our immune responses in both immune hot and immune cold tumors.